The Bear Grylls Adventure. Book 4, The Sea Challenge [anglicky] - Grylls, Bear (Bear Grylls Ventures, 2020)
The fourth in the fun new 12-book collectible series for young readers from survival expert and Chief Scout BEAR GRYLLS.Chloe is enjoying activity camp and all the outdoor fun - what's not to like?